HUBUNGAN KADAR GULA DARAH PUASA DENGAN PH SALIVA PADA PENDERITA DIABETES MELITUS (DM) TIPE 2 - Putri, Pande Ebin Anisa; Widyanthari, Desak Widyanthari Made; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing, 2021)
Saliva’s acidity (pH) has an important role in maintaining oral health. One of the factors that cause changes in salivary pH is the fasting blood sugar levels which caused by Type 2 Diabetes Mellitus (DM). This research was aims to determine the correlation of an increase in fasting blood sugar levels with changes of salivary pH in patients with type 2 DM in the work area of Puskesmas II Denpasar Timur. This study is a quantitative research that used correlative analytics design with cross-sectional study model approach. The sampling methods used purposive sampling which is a total of 30 respondents. The data collection of fasting blood sugar levels and salivary pH is done directly by the patients (door to door). Correlation test results using Pearson Product Moment, it showed that fasting blood sugar levels and salivary pH on patients with type 2 of DM in the work area of Puskesmas II Denpasar Timur has a weak and negative correlation (p = 0,03; r = -0,393), which means that the higher fasting blood sugar levels it will causes of decreasing salivary pH. This study is expected to be beneficial for who has type 2 DM to control their blood sugar levels so that oral health complications caused by decreasing of salivary pH could be prevented.